Influence of green inclusive leadership on sustainable performance through innovative behavior: Moderating role of green psychological climate and climate for inclusion - Asif Hussain Samo; Quratulain Nazeer Ahmed; Syed Aamir Alam Rizvi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This study explores the relationship between green inclusive leadership and sustainability performance with the mediating role of innovative behavior and the moderating role of green psychological climate and the climate of inclusion. Following the paradigm of positivism, this quantitative study collected data from 382 followers and 75 leaders from the health sector. The survey was conducted on reliable and valid instruments from the literature. Structural equation modeling through Smart PLS was used for data analysis. Results revealed that green, inclusive leadership impacts sustainable performance in the health sector directly and through innovative behavior. Moreover, a Green psychological climate and climate for inclusion moderate this relationship. The health sector that needs sustainable performance should cultivate green inclusive leadership at all levels and for that purpose, hospitals should initiate relevant training programs.
Keywords: 330; Climate for inclusion; green inclusive leadership; innovative behavior; green psychological climate; sustainability performance